Collection of Chilli Genetic Resources from different Geographical Regions of West Bengal, India - Paul, Subhabrata; Das, Anupam; Sarkar, N. C.; Ghosh, Biswajit (International Journal of Bio-resource and Stress Management, 2023)
West Bengal, India is immensely rich in plant biodiversity. The present study was undertaken for an exploration and collection mission for wild, semi-wild, and domesticated populations of Chilli germplasm collection was carried out from 2009 to 2012, a total eighty-eight accessions in 17 district of WB on the basis of their shape, size and color along with pungency which are always the selected characteristics feature of chilli. This collection was expanding the number of accessions of wild chilli that are publicly available for research in plant improvement, characterization, evaluation and for subsequent use in an inquiry into the domestication. The diversity could mainly be attributed to diverse agro climatic conditions in WB. The intraregional diversity could be as a valuable source as interregional diversity for chilli improvement. With the establishment of Seed Genebank we stored natural orthodox seeds in low temperature (4-60C) and low humidity condition.